Short-Time Ice Drift and Deformation Measurements Using Multi-Mission Synethetic Aperture Radar - Kræmer, Thomas; Brekke, Camilla (2015)
Norway is in a good position regarding frequent access to synthetic aperture radar data. A Norwegian– Canadian agreement provides large quotas of RADARSAT-2 images used operationally by e.g. the Norwegian Ice Service. More recently, Norway’s participation in the Copernicus program also allows rapid access to SENTINEL-1A data. By combining these data sources we can get satellite time series with very low time separation which allows us to study ice drift, deformation and ice growth processes with a time resolution of minutes and hours rather than days. This allows us to measure the drift of fast moving ice which is usually not observable due to insufficient time sampling. We study ice drift derived using varying time separations ranging from minutes to one day and show the effect on estimated ice speeds. The derived drift is used to construct deformation maps showing areas of converging and diverging ice. We show that very high time resolution is sometimes necessary for measuring fast moving ice. We focus on a particular example that illustrates how low time sampling implies missing significant changes in deformation within one day